2007
DOI: 10.1073/pnas.0707204104
|View full text |Cite
|
Sign up to set email alerts
|

Different transmitter transients underlie presynaptic cell type specificity of GABA A,slow and GABA A,fast

Abstract: inhibition ͉ neocortex ͉ neurogliaform cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
155
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(176 citation statements)
references
References 51 publications
20
155
0
1
Order By: Relevance
“…Indeed, the rate of spontaneous IPSCs mediated by "slow" GABA A receptors (GABA A, slow ) (Pearce, 1993), which may originate from neurogliaform interneurons (Price et al, 2005;Szabadics et al, 2007), has been reported to be selectively increased by low doses of NA (Banks et al, 2002). However, without a parallel effect on coupling, it would be difficult to explain how this powerful excitation of a GABAergic network would not translate into phasic synchronized epileptiform activity.…”
Section: Gap Junctions Of Hippocampalmentioning
confidence: 99%
“…Indeed, the rate of spontaneous IPSCs mediated by "slow" GABA A receptors (GABA A, slow ) (Pearce, 1993), which may originate from neurogliaform interneurons (Price et al, 2005;Szabadics et al, 2007), has been reported to be selectively increased by low doses of NA (Banks et al, 2002). However, without a parallel effect on coupling, it would be difficult to explain how this powerful excitation of a GABAergic network would not translate into phasic synchronized epileptiform activity.…”
Section: Gap Junctions Of Hippocampalmentioning
confidence: 99%
“…However, it remains to be investigated whether other interneurons innervating the perisomatic domain of pyramidal cells, such as axo-axonic and CCKexpressing interneurons, might provide differently timed GABAergic input during theta oscillations. Distinct GABAergic interneurons have been described to differentially modulate pyramidal cells and cell assemblies in vitro (Szabadics et al, 2007;Molnár et al, 2008). Recently, two populations of fast spiking interneuron, including PV-positive basket cells, were reported with different firing patterns in the frontal cortex in vivo (Puig et al, 2008).…”
Section: Prefrontal Pv؉/cb؉ Basket and Pyramidal Cell Firing In Vivomentioning
confidence: 99%
“…4) (Fuentealba et al, 2008). IvyCs belong to the family of neurogliaform cells that are known to provide powerful, long-lasting inhibition to postsynaptic cells through their extremely dense axonal cloud (Tamás et al, 2003;Price et al, 2005;Szabadics et al, 2007). However, in contrast to hippocampal neurogliaform cells (Price et al, 2005), IvyCs release GABA onto the proximal dendritic region of pyramidal cells as they innervate the inner portion of stratum radiatum and stratum oriens (Fuentealba et al, 2008).…”
Section: Specific Description Of Cell Typesmentioning
confidence: 99%
“…As far as MF input properties are concerned, CA3 IvyCs were most similar to RSBCs, displaying rare but strong MF-euEPSCs on a background of lowfrequency spontaneous synaptic events. Although the properties of CA3 IvyCs will need to be studied further, it is likely that MF inputs to IvyCs contribute to the regulation of pyramidal cell dendritic excitability during behaviorally relevant network rhythms (Fuentealba et al, 2008) through slow IPSPs characteristic of neurons in the neurogliaform cell family (Tamás et al, 2003;Price et al, 2005;Szabadics et al, 2007).…”
Section: Mf Inputs To Slcs and Ivycsmentioning
confidence: 99%